2020
DOI: 10.1038/s41598-020-76391-w
|View full text |Cite
|
Sign up to set email alerts
|

Comparing distress of mouse models for liver damage

Abstract: In order to foster animal welfare as well as high quality of research, many countries regulate by law that the severity of animal experiments must be evaluated and considered when performing biomedical research. It is well accepted that multiple parameters rather than a single readout parameter should be applied to describe animal distress or suffering. However, since the performance of readout parameters for animal distress is rarely defined and methods for multivariate analysis have only in rare cases been u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 52 publications
2
17
0
Order By: Relevance
“…Therefore, the early phase and the late experimental phase were chosen as time points to assess the distress using additional parameters. As seen in other studies on distress and weight change [ 23 ], when mice suffered severe distress, the body weight of the experimental animals started to decrease progressively. Although the surgery itself had an impact on the welfare of the mice, the noticeable increase in body weight at the late phase indicated that the mice were in good condition, and that the AVF itself did not cause severe distress to the animals.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…Therefore, the early phase and the late experimental phase were chosen as time points to assess the distress using additional parameters. As seen in other studies on distress and weight change [ 23 ], when mice suffered severe distress, the body weight of the experimental animals started to decrease progressively. Although the surgery itself had an impact on the welfare of the mice, the noticeable increase in body weight at the late phase indicated that the mice were in good condition, and that the AVF itself did not cause severe distress to the animals.…”
Section: Discussionsupporting
confidence: 70%
“…Continuous observation of body weight revealed that there was a weight loss in the early phase, which could be explained by surgery. Surgery and anesthesia are both particularly potent stressors [ 21 , 22 ], and thus post-surgical body weight reduction is common in mice [ 16 , 23 , 24 , 25 ]. However, as the experiment progressed, the mice recovered and gained stable weight over the next 3 weeks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Water and standard laboratory chow were provided ad libitum. Mice were bred under specific germ-free conditions (except for the following pathogens detected within the last two years, i.e., Helicobacter sp., Rodentibacter pneumotropicus, murine Norovirus and rat Theilovirus) in individually ventilated cages and with environmental enrichment [20]. Mice were group-housed during breeding and for the experiments, different numbers of mice (N = 2-5) were housed in cages and different litters were used.…”
Section: Ethics Statementmentioning
confidence: 99%
“…The parameters of interest have been selected based on consortium data, which were obtained in adult rodent disease models, and which supported an informative value for the purpose of severity assessment (e.g. 8 , 9 , 12 20 ). Information about model-specific characteristics provide key elements for an evidence-based grading of severity, and allow filling of gaps in model-specific refinement recommendations 8 .…”
Section: Discussionmentioning
confidence: 99%